2015
DOI: 10.1021/jp510775e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Stabilization of Helix Secondary Structure by Constrained Cα-Tetrasubstituted α-Amino Acids

Abstract: The theoretical basis behind the ability of constrained Cα-tetrasubstituted amino acids (CTAAs) to induce stable helical conformations has been studied through Replica Exchange Molecular Dynamics Potential of Mean Force Quantum Theory of Atoms In Molecules calculations on Ac-l-Ala-CTAA-l-Ala-Aib-l-Ala-NHMe peptide models. We found that the origin of helix stabilization by CTAAs can be ascribed to at least two complementary mechanisms limiting the backbone conformational freedom: steric hindrance predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 99 publications
4
40
0
Order By: Relevance
“…In the case of benzaldehyde and 4-NO 2 -benzaldehyde, different enantioselectivities were observed depending on the catalyst geometry. Indeed, low enantioselectivity was obtained by using B, B1 and C complexes that would lead to a bidentate complex and in which the peptides do not assume a stable b-turn conformation (entries [7][8][9][10][11][12][13][14][15]. This behavior might depend on the higher molecular mobility of these complexes making them capable to accommodate different labile geometries.…”
Section: Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of benzaldehyde and 4-NO 2 -benzaldehyde, different enantioselectivities were observed depending on the catalyst geometry. Indeed, low enantioselectivity was obtained by using B, B1 and C complexes that would lead to a bidentate complex and in which the peptides do not assume a stable b-turn conformation (entries [7][8][9][10][11][12][13][14][15]. This behavior might depend on the higher molecular mobility of these complexes making them capable to accommodate different labile geometries.…”
Section: Peptidementioning
confidence: 99%
“…On the other hand, reproducing the functional groups' spatial arrangement of a catalytic site with small peptides is still a challenge. [8][9][10] Metal transporters are proteins 11,12 devoted to the trafficking of ions across the membranes and contain peptide domains able to bind metal ions. [13][14][15][16][17][18] A powerful approach to design hybrid metalpeptide catalysts could thus take advantage of the modulation of their binding activity.…”
mentioning
confidence: 99%
“…Indeed, REMD simulations, followed by cluster analysis, showed that only the central portion of the peptide maintained a helical secondary structure, while the first two residues at the N‐terminus and the last four at the C‐terminus, were disordered (Figure A). Aiming to stabilize the helical conformation, without affecting the binding capabilities of the peptide to Rac1, we evaluated the mutation of the N‐terminal I1187 to the non‐natural amino acid NRB (Figure B), which in previous theoretical works showed a discrete capability of stabilizing α‐helices and a good propensity in inducing a right‐handed helix screw sense . Among other non‐natural amino acids, NRB was also chosen as a mimetic of aliphatic apolar amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…53 To understand if this interaction can be considered as a true H-bond, we performed a quantum theory of atoms in molecules (QTAIM) analysis on the most representative geometry of cluster1, previously optimized in the gas phase by density functional theory (DFT) using the mPW1B95/6-31+G(d,p) level of theory, as done in previous works. 41,43,54 Interestingly, we observed a bond critical point (BCP) and a bond path connecting NHLeu to β-Morph oxygen (Figure S17, ESI). The BCP density ρ(rc) = 0.021 a.u.…”
Section: Scheme 1 Synthesis Of Compoundmentioning
confidence: 96%
“…In previous works, we used temperature replica exchange molecular dynamics (T-REMD) 39 to model linear and cyclic peptides containing non-coded amino acids. 17,18,33,36,[40][41][42][43][44][45] In this work, we simulated peptides in acetonitrile solution to obtain a computational model as close as possible to experimental NMR conditions. Although T-REMD simulations can be performed with explicit solvation, they have a computational cost which can be prohibitive, since the number of required replicas is proportional to the number of particles in the system.…”
Section: Scheme 1 Synthesis Of Compoundmentioning
confidence: 99%